Development and scale-up of fully printable perovskite solar modules - SIMONE MERONI (2021)
Perovskite solar cells represent a new class of photovoltaic devices that, in only a decade, has already been achieved comparable performance to that of the most established photovoltaic technologies. To satisfy the demanding market require-ments, however, perovskite solar cells need to have the high performances with the use of low-cost materials and cost-eﬀective fabrication processes, during a long term in the working environment and this needs to be possible for both small scale and large-scale devices.The fully printable carbon perovskite solar cells are based on an inorganic triple mesoscopic stack that is inﬁltrated by a perovskite precursors solution. This architecture seems to be the most promising to satisfy the requirements of the market, because the manufacture can simply occur with low-cost materials and well-established industrial deposition techniques, such as screen printing. Further-more, the stability of these cells was reported to be one of the longest among perovskite solar cells, making this technology the closest to make market penetra-tion.This work focuses on fully printable perovskite solar cells with a special outlook at their up-scaling in series-connected modules. The fabrication of large area modules with both high performance and substrate coverage will be discussed, in a journey that starts from single cell devices, overcomes issues found in the up-scaling process, and ﬁnally reaches design optimisation. Devices of single cells with 1 cm2 active area will be presented, as well as modules on 5 × 5 cm2 or 10 × 10 cm2 substrates. Finally, series-connected modules with around 200 cm2 active area and high coverage on the substrate will be shown.